2021
DOI: 10.26512/sersocial.v23i48.33812
|View full text |Cite
|
Sign up to set email alerts
|

Daily Menu in Times of Pandemic for Individuals with Anxiety and Depression

Abstract: The COVID-19 pandemic brought to light food and nutrition vulnerabilities in society, which were aggravated by the effects of social isolation and other measures to contain coronavirus spread in people’s lives. This study explores how individuals with mental disorders are reacting to this pandemic time, focusing in the context of their eating habits. For that, nineteen in-depth interviews were conducted with people previously diagnosed with depression and/or anxiety. We found out that the pandemic affected foo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…An unhealthy diet is associated with depression (Meller et al , 2021). Alcoforado et al (2021) investigated how people with anxiety and depression in Brazil are more vulnerable to unhealthy foods and binge eating, both driven by emotional consumption, that is, eating in response to negative emotions. In our research, Brazilian depressives reported consuming more pasta, cookies, sweets and sandwiches than Brazilians without a level of the disease.…”
Section: Findings and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An unhealthy diet is associated with depression (Meller et al , 2021). Alcoforado et al (2021) investigated how people with anxiety and depression in Brazil are more vulnerable to unhealthy foods and binge eating, both driven by emotional consumption, that is, eating in response to negative emotions. In our research, Brazilian depressives reported consuming more pasta, cookies, sweets and sandwiches than Brazilians without a level of the disease.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Also, because of the symptoms and consequences of the disease, depression is related to a higher medication intake, such as antidepressants, anxiolytics, sleeping pills and opioids (Kodaira et al ., 2015; Scherrer et al , 2020). In addition, it has been already investigated the low rate of physical activity by depressed individuals and the higher intake of unhealthy food (Alcoforado et al , 2021; Meller et al ., 2021; Zhang et al , 2021). According to Maddock and Hill (2016), foods not only affect mood and general well-being but also contribute to the prevention and treatment of specific mental disorders.…”
Section: Background and Research Hypothesesmentioning
confidence: 99%